Літератори та "червоні моряки" проти "червоних комісарів": два тижні миколаївської "матроської республіки" (14-27 травня 1919 р.) - Савченко, В. (Краєзнавство, 2018)
В статті вперше в історіографії аналізуються причини, цілі, хід збройного виступу моряків проти
диктатури більшовиків у місті Миколаєві в травні 1919 р., а також розглядається структура влади, яка сформувалася під час повстання, роль ідеологів повстання Я. Плешкевича та С. Юріцина, вперше аналізуються публікації газет повстанців «Свободное слово красного моряка». In the article, for the first time in historiography, the reasons, objectives and the course of the armed insurrection
of sailors against the dictatorship of the bolsheviks in Nikolaev in May of 1919 are analyzed. The uprising of
the sailors in Nikolaev was the first rebellion in the navy of the so-called «third force» (the «third revolution»), the
design of which began with the insurrection of Ataman Grigor'ev and the Makhnovist movement in the spring and
summer of 1919, the last splash of which was the Kronstadt Uprising of Sailors of 1921. There was a unique situation
in Nikolaev when parts of sailors and soldiers of the Red Army were in favor of a broad political coalition, freedom
of trade and were against the power of the one party and the repression of the Cheka. The structure of power
that emerged during the uprising, the role of the ideologists of the Y. Pleshkevich and S. Yuritsin, sailors' leaders
were considered in this article. For the first time, the publication of two issues of the newspaper «The Free Speech
of the Red Sailor» published by the insurgents is being analyzed. The events in Mykolayiv are considered in the context
of the events in the South of Ukraine in May of 1919: the situation that was on the fronts and rearward of the
Red Army, uprisings in Kherson, Odessa and Ochakov, peasant demonstrations against the policy of «war communism
». An analysis of the events shows how the regime of the Bolsheviks was shaky and did not have a broad support
among the masses, revealing the concealed sharpness of the political struggle within the «revolutionary
camp» and the unique political mobility of those days. The insurrection became a manifestation of the general
processes that shook Ukraine, in the era of revolutionary activity, when the people were looking for new forms of
state and social organization. В статье впервые в историографии анализируются причины, цели, ход вооруженного восстания моряков против диктатуры большевиков в городе Николаев в мае 1919 г., рассматривается структура власти, которая сложилась в ходе восстания, роль идеологов восстания Я.
Плешкевича и С. Юрицина, впервые анализируются публикации газеты восставших «Свободное
слово красного моряка».